Consequences of testing for mismatch repair deficiency of colorectal cancer in clinical practice. (4th May 2018) - Leicher, L. W.; Lammertink, M. H. A.; Offerman, S. R.; Morreau, H.; de Jong, M. M.; de Groot, J. W. B.; van Westreenen, H. L.; Vasen, H. F. A.; de Vos tot Nederveen Cappel, W. H.
Abstract: Introduction: Mismatch repair deficiency (dMMR) can be found in Lynch syndrome (LS)-associated colorectal carcinoma and in 15% of sporadic colorectal cancer (CRC). Outcome of MMR-deficiency testing is important for surgical decisions as extended colectomy is recommended in young LS-patients with CRC. Moreover, the finding of a dMMR tumour has consequences for the choices of adjuvant chemotherapy as MMR-deficient CRC is resistant to 5-fluorouracil (5-FU) monotherapy. Aims of our study are to evaluate whether MMR-deficiency testing leads to (1) identification of LS, (2) change in surgical treatment and (3) adjustment of systemic therapy in patients with dMMR CRC. Methods: We performed a multicentre, retrospective study, in a community hospital and a University Medical Centre. We included all CRC-patients between 2012 and 2016 who were tested for microsatellite instability. We collected clinical data such as gender, age, referral to clinical geneticist, surgical procedure and choice of chemotherapy. Results: We analysed 225 CRCs. Twenty-four (10.7%) of 225 CRC were MMR-deficient. Of the 24 patients with dMMR CRC, 18 (75%) were referred to the clinical geneticist and in nine (37%) patients a MMR mutation was identified. In one (4%) of the 24 patients, a subtotal colectomy was performed. In seven (35%) out of 20 MMR deficient patients, the chemotherapy regimen was adjusted. Conclusions: The finding of a dMMR CRC had consequences for decisions on chemotherapy in a relative high proportion of patients. We recommend testing in all patients with CRC independent of age at diagnosis, as proper treatment decisions and genetic counselling are very important.